Building Customer Satisfaction through Trust: Service Quality, Perceived Value, and Experience at SPKLU UB Disyan PLN Batam: Membangun Kepuasan Pelanggan melalui Kepercayaan: Kualitas Layanan, Nilai yang Dirasakan, dan Pengalaman di SPKLU UB Disyan PLN Batam - Daniel Kasidi; Ayu Puspitasari; Natasha Salsabilah; Viona Metriani; Adhitomo Wirawan (Universitas Muhammadiyah Sidoarjo, 2026)
Customer satisfaction represents a critical indicator of service performance and organizational sustainability in service-based industries. In the electric vehicle charging services, customer satisfaction not only reflects customers evaluative judgments of service encounters but also determines their intention to continue usage and maintain long-term relationships with the provider. This study examines the interconnections among service quality, perceived value, customer experience, trust, and customer satisfaction at SPKLU UB Disyan PLN Batam. The population of this study consists of the people of Batam City, particularly users of the SPKLU UB Disyan PLN Batam service. The study aims to analyze the influence of service quality, perceived value, and customer experience on customer satisfaction, with trust serving as a mediating variable. This research employed a quantitative approach using survey data collected from 155 respondents selected through nonprobability purposive sampling, namely customers who had used the SPKLU service within the last six months. This sampling technique is appropriate because the study requires respondents who have direct experience with SPKLU services, ensuring that the data collected are relevant and reflective of actual service evaluations. Purposive sampling is widely used in service research where specific criteria are necessary to obtain valid and meaningful insights. Data were analyzed using Structural Equation Modeling–Partial Least Squares. The results indicate that service quality, perceived value, and customer experience have positive and significant effects on customer satisfaction. These findings emphasize the importance of enhancing service performance and building customer trust to improve customer satisfaction in electric vehicle charging services in Batam City.